20 years of information technology agreement : boosting trade, innovation and digital connectivity - Tang, Xiaobing (WTO GenevaCH, 2017)
Reviews new developments, such as the landmark deal concluded in 2015 to eliminate tariffs on an additional 201 IT products valued at over